Dual-targeted therapy with trastuzumab and lapatinib in treatment-refractory, KRAS codon 12/13 wild-type, HER2-positive metastatic colorectal cancer (HERACLES): a proof-of-concept, multicentre, open-label, phase 2 trial. Issue 6 (June 2016) - Sartore-Bianchi, Andrea; Trusolino, Livio; Martino, Cosimo; Bencardino, Katia; Lonardi, Sara; Bergamo, Francesca; Zagonel, Vittorina; Leone, Francesco; Depetris, Ilaria; Martinelli, Erika; Troiani, Teresa; Ciardiello, Fortunato; et al.
Summary: Background: We previously found that dual HER2 blockade with trastuzumab and lapatinib led to inhibition of tumour growth in patient-derived xenografts of HER2 -amplified metastatic colorectal cancer. In this study, we aimed to assess the antitumour activity of trastuzumab and lapatinib in patients with HER2-positive colorectal cancer. Methods: HERACLES was a proof-of-concept, multicentre, open-label, phase 2 trial done at four Italian academic cancer centres. We enrolled adult patients with KRAS exon 2 (codons 12 and 13) wild-type and HER2-positive metastatic colorectal cancer refractory to standard of care (including cetuximab or panitumumab), an Eastern Cooperative Oncology Group performance status of 0 or 1, and at least one measurable lesion. We defined HER2 positivity in tumour samples by use of immunohistochemistry and fluorescence in-situ hybridisation in accordance with our previously validated colorectal cancer-specific diagnostic criteria. Eligible patients received intravenous trastuzumab at 4 mg/kg loading dose followed by 2 mg/kg once per week, and oral lapatinib at 1000 mg per day until evidence of disease progression. The primary endpoint was the proportion of patients achieving an objective response (defined as complete response or partial response), which was assessed by independent central review in the intention-to-treat population. This trial is registered with EudraCT, number 2012-002128-33. Findings: Between Aug 27, 2012, and May 15, 2015, we screened 914 patients with KRAS exon 2 (codons 12 and 13) wild-type metastatic colorectal cancer and identified 48 (5%) patients with HER2-positive tumours, although two died before enrolment. Of these patients, 27 were eligible for the trial. All were evaluable for response. At the time of data cutoff on Oct 15, 2015, with a median follow-up of 94 weeks (IQR 51–127), eight (30%, 95% CI 14–50) of 27 patients had achieved an objective response, with one patient (4%, 95% CI −3 to 11) achieving a complete response, and seven (26%, 95% CI 9–43) achieving partial responses; 12 (44%, 95% CI 25–63) patients had stable disease. Six (22%) of 27 patients had grade 3 adverse events, which consisted of fatigue in four patients, skin rash in one patient, and increased bilirubin concentration in one patient. No grade 4 or 5 adverse events were reported. We detected no drug-related serious adverse events. Interpretation: The combination of trastuzumab and lapatinib is active and well tolerated in treatment-refractory patients with HER2-positive metastatic colorectal cancer. Funding: Associazione Italiana Ricerca Cancro (AIRC), Fondazione Oncologia Niguarda Onlus, and Roche.